Interobserver variation in respiratory signs of severe malaria. Issue 4 (April 1995) - English, M; Murphy, S; Mwangi, I; Crawley, J; Peshu, N; Marsh, K
Abstract : Respiratory abnormalities are common presentations of malaria and acute respiratory tract infection, both of which are major causes of childhood mortality and morbidity in sub-Saharan Africa. Appropriate management depends on accurate assessment of disease severity which for the majority of children must be based on clinical signs alone. Choosing which signs best serve this purpose remains a considerable problem particularly in malaria endemic areas. As part of a prospective study to define clinical signs indicative of life threatening malaria video recordings were used to examine the level of agreement between clinicians for potentially important respiratory signs in 51 children. Overall agreement was good for recession, severe recession, and nasal flaring (kappa = 0.57, 0.50, and 0.60 respectively) and substantial for deep breathing and the summary impression of respiratory distress (kappa = 0.70 and 0.69 respectively). However, within this substantial variation in interpretation was apparent between individual observers from slight to almost perfect agreement (kappa values 0.10-0.92). Video is a useful tool to demonstrate interobserver variation and it may also allow training in recognition of signs and a means of standardising clinical signs between centres.